Microwave-assisted Solid State Synthesis of Cathode Materials Incorporating Chitin for Lithium Iron Phosphate Batteries - Ekawat Ratchai (Prince of Songkla University, 2023)
Doctor of Philosophy (Sustainable Energy Management), 2022